Experimental Preparation and Numerical Simulation of High Thermal Conductive Cu/CNTs Nanocomposites - ., Ali Samer Muhsan, Faiz Ahmad, Norani M Mohamed, Puteri Sri Melor (2014)
Due to the rapid growth of high performance electronics devices accompanied by overheating problem, heat dissipater nanocomposites material having ultra-high thermal conductivity and low coefficient of thermal expansion was proposed. In this work, a nanocomposite material made of copper (Cu) reinforced by multi-walled carbon nanotubes (CNTs) up to 10 vol. % was prepared and their thermal behaviour was measured experimentally and evaluated using numerical simulation. In order to numerically predict the thermal behaviour of Cu/CNTs composites, three different prediction methods were performed. The results showed that rules of mixture method records the highest thermal conductivity for all predicted composites. In contrast, the prediction model which takes into account the influence of the interface thermal resistance between CNTs and copper particles, has shown the lowest thermal conductivity which considered as the closest results to the experimental measurement. The experimentally measured thermal conductivities showed remarkable increase after adding 5 vol.% CNTs and higher than the thermal conductivities predicted via Nan models, indicating that the improved fabrication technique of powder injection molding that has been used to produced Cu/CNTs nanocomposites has overcome the challenges assumed in the mathematical models.